Level of Engagement on Shared Governance in Public Elementary Schools - Miranda, Ronashiel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the level of engagement in shared governance among stakeholders in public elementary schools in the District of Baras, Division of Rizal, during the School Year 2025–2026. Utilizing a descriptive survey research design, the study involved three groups of respondents: school officials, parents, and Local Government Unit (LGU) members. A total of 144 school officials and 144 LGU members, representing 50% of their respective populations, were selected, while 285 parent-respondents were determined using Slovin’s formula. Data were gathered through a researcher-made questionnaire-checklist and analyzed using appropriate statistical tools.Findings revealed that respondents were generally “often engaged” in shared governance practices in terms of participation in decision-making, communication and collaboration, and transparency and accountability. However, certain profile variables significantly influenced engagement levels. Among school officials, educational attainment, length of service, in-service training, and age showed significant differences. For parents, educational attainment, occupation, income, age, and civil status were significant in selected domains. Among LGU members, civil status influenced engagement in communication and collaboration. Conversely, variables such as sex and some demographic factors were not significant predictors.The study also identified that stakeholders “sometimes” encountered challenges, including limited understanding of shared governance, unclear roles, and scheduling conflicts affecting participation. The study concluded that while engagement is evident, there is a need to strengthen stakeholders’ capacities and awareness.It is recommended that school administrators implement orientation programs, capacity-building activities, and establish effective communication channels. Flexible participation mechanisms and continuous monitoring are also encouraged to enhance stakeholder involvement. The proposed action plan is suggested for implementation, and further studies are recommended to explore additional variables affecting shared governance..
Keywords: shared governance, stakeholder engagement, public elementary schools, decision-making, communication and collaboration, transparency and accountability